(untitled) (Research, Society and Development, 2020)
The present work aims to report the reality and the difficulties faced by children, from the municipal public network of the city of João Pessoa during the pandemic of COVID-19 in 2020. The Povo Sem Medo de Lutar Camp, is located in Bairro das Industrias, Municipality of João Pessoa, Paraíba. In it, there are 42 two families and 65 children who live in a state of social vulnerability, without any support from the municipal education system. The camp leader built a school with canvas and donated materials so that the children would not be left without the routine of a school and without studying. In our theoretical field, we seek legal documents such as the 1988 Constitution, the Law of Directives and Bases of Education and authors such as Paulo Freire, Bourdieu, Marx and Saviani, to base the reflection on the reality of these families and children. We denounce the negligence of the municipal public authorities and the Municipal Education Secretariat, for not offering food or pedagogical support for the children who are part of the settlement.